2009
DOI: 10.1007/s00464-009-0618-9
|View full text |Cite
|
Sign up to set email alerts
|

Robotic gastrectomy for gastric cancer: surgical techniques and clinical merits

Abstract: Robotic gastrectomy for the treatment of gastric cancer is a feasible and safe procedure in the hands of experienced laparoscopic surgeons. Robotic gastrectomy offers better short-term surgical outcomes than the open and laparoscopic methods. Furthermore, this procedure may be a preferable alternative for the treatment of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 27 publications
5
160
1
1
Order By: Relevance
“…The advantages of robotic surgery include a 3D imagine, convenient movements of the robotic arm, no tremor, and ambidextrous capability (Baik et al, 2009;Kim et al, 2010;Buchs et al, 2011). Robotic surgery is now widely performed in the fields of gynecology, urology and general surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of robotic surgery include a 3D imagine, convenient movements of the robotic arm, no tremor, and ambidextrous capability (Baik et al, 2009;Kim et al, 2010;Buchs et al, 2011). Robotic surgery is now widely performed in the fields of gynecology, urology and general surgery.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6 Robotic EndoWrist Ⓡ (Intuitive Surgical) enables meticulous lymph node dissection, which allows complete D2 lymphadenectomy. 2,[4][5][6] Partial nephrectomy has been performed to treat incidental small renal masses. Many studies reported the advantages of robotassisted partial nephrectomy using EndoWrist Ⓡ in intracorporeal suturing.…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted surgery is performed in many hospitals, especially for early stages of cancers. [1][2][3] However, reports on robot assisted combined operations are very limited. We report the first successful concurrent robotassisted distal gastrectomy and partial nephrectomy in a patient with synchronous early gastric cancer and renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…in 2003. Since then, a few small series have been reported that show relatively good short-term results comparable to those obtained with laparoscopic or conventional open surgery [27][28][29][30][31][32][33][34][35][36][37] . In 2009, Song et al [32] presented their initial 100 cases of robot-assisted gastrectomy with lymph node dissection; it is the largest series for robotic surgery with gastric cancer in the literature.…”
Section: Practicementioning
confidence: 94%